2013
DOI: 10.5114/pdia.2013.33375
|View full text |Cite
|
Sign up to set email alerts
|

Oral retinoids and rexinoids in cutaneous T-cell lymphomas

Abstract: Retinoids are biologically active derivatives of vitamin A modulating cell proliferation, differentiation, apoptosis and altering the immune response. They have been used for years in therapy of cutaneous T-cell lymphomas (CTCL) but the exact mechanism of retinoids’ action is unclear. It is based on the presence of specific receptors’ families, mediating the biological effects of retinoids on the tumor cells: retinoic acid receptor (RAR) and retinoic X receptor (RXR). Orally administrated bexarotene, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…1 Transactivation of some of these other nuclear receptors is believed to be linked to some of the side effects seen with the retinoids. 1 Despite significant progress in elucidating the mechanism by which retinoids exert their activity, their effect on tumorigenesis and cancer biology remains poorly understood. The RAR receptors bind only to all-trans retinoid acid, 9-cis retinoic acid or synthetic isotretinoin, etretinate, and acitretin.…”
Section: Retinoids and Mechanism Of Actionmentioning
confidence: 98%
See 3 more Smart Citations
“…1 Transactivation of some of these other nuclear receptors is believed to be linked to some of the side effects seen with the retinoids. 1 Despite significant progress in elucidating the mechanism by which retinoids exert their activity, their effect on tumorigenesis and cancer biology remains poorly understood. The RAR receptors bind only to all-trans retinoid acid, 9-cis retinoic acid or synthetic isotretinoin, etretinate, and acitretin.…”
Section: Retinoids and Mechanism Of Actionmentioning
confidence: 98%
“…Each receptor is associated with 3 subtypes, a, b, and, g, which bind to specific ligands. 1,14 These receptors are part of a larger superfamily of nuclear receptors, including thyroid hormone receptor, vitamin D3 receptor, and glucocorticoid receptor ( Table 1). 1 Transactivation of some of these other nuclear receptors is believed to be linked to some of the side effects seen with the retinoids.…”
Section: Retinoids and Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of Targretin action has yet to be fully elucidated. It has been shown that the drug can induce apoptosis, differentiation and cellular senescence, inhibit metastasis and angiogenesis, and block cell cycle progression, which was reviewed recently [73][74][75][76].…”
Section: Rexinoids and Cancer Therapymentioning
confidence: 99%